Potential Hazards and Associated Causal Factors in the Occupational Environment of Palm Oil Workers - Istisya, Afifah Salsabilla; Denny, Hanifa Maher; Setyaningsih, Yuliani (Universitas Airlangga, 2024)
Introduction:Palm oil workers are exposed to numerous hazards in the work environment associated with accidents and occupational diseases. Work-related accidents are typically influenced by a combination of internal and external factors. Therefore, this study aimed to analyze the potential hazards and influencing factors affecting the safety of workers in palm oil gardens. Method: PRISMA guidelines with Boolean operators were used alongside specified keywords